A General Method for Extracting Individual Coupling Constants from Crowded 1H NMR Spectra. Issue 3 (4th December 2015) - Sinnaeve, Davy; Foroozandeh, Mohammadali; Nilsson, Mathias; Morris, Gareth A.
Abstract: Couplings between protons, whether scalar or dipolar, provide a wealth of structural information. Unfortunately, the high number of 1 H‐ 1 H couplings gives rise to complex multiplets and severe overlap in crowded spectra, greatly complicating their measurement. Many different methods exist for disentangling couplings, but none approaches optimum resolution. Here, we present a general new 2D J‐resolved method, PSYCHEDELIC, in which all homonuclear couplings are suppressed in F 2, and only the couplings to chosen spins appear, as simple doublets, in F 1 . This approaches the theoretical limit for resolving 1 H‐ 1 H couplings, with close to natural linewidths and with only chemical shifts in F 2 . With the same high sensitivity and spectral purity as the parent PSYCHE pure shift experiment, PSYCHEDELIC offers a robust method for chemists seeking to exploit couplings for structural, conformational, or stereochemical analyses. Abstract : Finding a needle in a haystack : Measurement of 1 H‐ 1 H couplings in very crowded 1 H NMR spectra is made straightforward by a general new method, PSYCHEDELIC. This resolves individual couplings at near‐ideal resolution, without interference from other splittings, with good tolerance to strong coupling, and at high sensitivity.